Measurement Of Overall Equipment Effectiveness (OEE) IMC Machine at Sugar Factory PT. ABC - Aan Zainal Muttaqin; Mushtofa Lutfil Anshori (Cita Konsultindo Research Center, 2023)
PT ABC sugar factory is one of the business units of PTPN XI in the western region of East Java. During the milling period in 2022, the production process at the milling station often experiences a downtime process so that it disrupts the production process which hampers the sugar manufacturing process. The high downtime affects the yield of sugar capacity produced during the production process. The study was held to measure Overall Equipment Effectiveness (OEE) during the production process at the mill station on the IMC machine which functions as a medium for transporting chopped sugar cane to the juice press machine. The result of measuring the Overall Equipment Effectiveness value on the IMC machine produces a value of <85% as a standard value in the world.